Analisis visualisasi ekspresi kabasaran pada komik digital Nusantara Droid War - apsari hasan (Pixel :Jurnal Ilmiah Komputer Grafis, 2021)
This study aims to identify and analyze the visualization of the expression of the main character of the droid, namely Kabasaran in the digital comic Nusantara Droid War using a visual language approach through the wimba 4 method (illustration). Visual analysis includes elements and principles of visual language by classifying Kabasaran character expressions based on the suitability of the form language method. The results of the analysis show the depiction of expressions, using detailed line drawings and thin shading on the eyes, eyebrows, nose and mouth. The way of depiction in Kabasaran expression uses expressive depiction, distortion, and lines. Expressive drawing uses lines that give the effect of wrinkles between the eyes. Enlarged distortion depiction, used for the eyes, mouth, and teeth. Overall, the face is described as smooth, not many thick lines that give the impression of wrinkles or an old impression which is adapted to the character of Kabasaran in the comic, which is a small child. Keywords: Expression Visualization, Visual Language, Form Language